WAYS TO IMPROVE THE PHYSICAL FITNESS THROUGH AEROBIC GYMNASTICS MEANS - Zaharia A.M; Rață G. (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2013)
This research aimed to study the probable effects that aerobic gymnastics could have on the body, for improving the physical fitness. The main goal of the research was to identify the effects the aerobic gymnastics has in improving physical fitness.This research was conducted on 15 subjects between 18 and 30 years old, who participated in aerobic gymnastics fitness-type lessons, three times a week. The programs comprised exercises of physical development , stretching and elasticity, of relaxation, of coordination, and not in the least, of muscle strengthening. In order to evaluate the effectiveness of the applied means, the Ruffier test was used to assess the physical fitness of the subjects, and the Dorgo Index, to assess the cool-down response. The research data emphasized the subjects' interest for their physical fitness through a dynamic activity, constituting an argument for the practice of aerobic gymnastics throughout one's entire life, as a mean to preserve one's youth and beauty.